Post feeding protection from Bilimbi to Motile Aeromonas Septicemia disease in African Catfish - Sefti Heza Dwinanti; Gusti Setiawan; Ade Dewi Sasanti; Madyasta Anggana Rarassari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Bilimbi (Averrhoa bilimbi) is plant medicinal used to control fish diseases both prevention and treatment. This study aims to determine the protection period of bilimbi-fed which different duration in catfish to enhance catfish (Clariassp.) immunity in order to protect fish fromAeromonas hydrophilainfection. The Randomized Block Design Factorial (RBDF) with 2 factors was used in this experimental. The first factor (A) was the period of feeding containing bilimbi juice consisting of 3 treatments, namely 0 days (P0), 7 days (P1), and 14 days (P2). The second factor (B) was the protection period after the administration of bilimbi juice to the infection ofA. hydrophilabacteria consisting of 3 treatment, 5 days (T5), 10 days (T10), and (T15). This research was conducted at the Laboratory of Aquaculture Experiment Pond, Faculty of Agriculture, Sriwijaya University in October-December 2018. The parameters observed included prevalence of infection, growth, survival, feed efficiency and water quality. The result revealed that by giving 300 mL.kg-1 of bilimbi juice with different periods significantly affected the period of fish protection forA. hydrophilainfection.The best prevalence value was 3,33% (P2T5),and the best survival of the fish before infection was 94,17% (P2), while the best fish survival post infection was 100% (P2T5), the best feed efficiency value was 56,47% (P2), water quality under experiment were 26-29,70C for temperature, pH 6.8-7.7, dissolved oxygen 4.35-5.37 mg/L and ammonia 0.09-0.21 mg/L.Keywords:Averrhoa bilimbiAeromonas hydrophilaEthnomedicinal plantFish immunityMotile Aeromonas Septicemia